Ageing and cognition in men with fragile X syndrome - Oili Sauna-aho; Nina Bjelogrlic-Laakso; Päivi Rautava; Maria Arvio (WILEY, 2022)
Background Fragile X syndrome (FXS) is the most common inherited cause of intellectual disability. The aim of our longitudinal study was to describe ageing-related cognitive changes in men with FXS.
Method A neuropsychologist determined the raw scores (RSs) of 19 men with FXS twice with the Leiter International Performance Scale at an average interval of 22 years. The ages of the participants at baseline ranged from 16 to 50 (mean 27) years.
Results At follow-up, the RSs improved in two men, remained the same in two men and declined in 15 men. Overall, the RS of the study group deteriorated by an average 4 points in RSs (p < .001).
Conclusion Cognitive ageing in men with FXS started earlier than that in men in the general population; in many cases, cognitive ageing in men with FXS began before middle age, usually without any medical or other underlying cause.